Analyzing the effects of 16 weeks swimming exercises of children aged 7-13 on anthropometric measurements and somatotype - Defne Ocal Kaplan (Türk Spor ve Egzersiz Dergisi)
By the carried study, it’s aimed to expose the effects of 16 weeks swimming exercises of sedentary girl and boys aged 7-13 on anthropometric measurements and somatotype components. In total 114 children, healthy 53 girls, the average age 9.35±2.14 years and 61 boys, the average age 9.56±2.74 years under the summer school joining to swimming lessons participated to this research. Height, body mass, chest, waist and hip circumference measurements and 10 anthropometric measurements of research group necessary for somatotype calculation has taken before and after the 16 weekly swimming program. Somatotype calculations evaluated by Heath-Carter somatotype method. Data tested in p lt;0.05 significance level via Paired Samples t-Test. With the data obtained before and after swimming exercises, as compared to boys and girls separately, all the data apart from height, medial calf skinfold, waist/hip ratio, mesomorph coefficient in girls and all the data apart from height and waist/hip ratio are significantly different in boys. Somatotype values in preliminary test of girls changed from 4.99-3.64-2.35 to 4.45-3.78-2.8 and of boys changed from 4.67-3.72-2.24 to 3.92-4.15-2.38. The findings of the study show that swimming exercises have effects on the decrease in body mass and increase in muscle mass. Given the characteristics of the investigated age group, the period of pre-adolescent girls tend to increase the lubrication, swimming exercises to be held in this age group would benefit for weight control and create a healthier future generation. Swimming exercises are important for preventing weight gain and deal with existing problems of technology and inactivated lifestyle especially in the puberty period children.